1994
DOI: 10.1111/j.1365-2052.1994.tb00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic blood markers in Arabian, Barb and Arab‐Barb horses in Morocco

Abstract: Summary Gene frequencies at 16 blood group and protein polymorphism loci (A, C, D, K, P, Q, U, Al, Gc, Es, A1B, Tf, PGD, PGM, GPI and Pi) are given for three horse breeds in Morocco (Arabian, Arab‐Barb and Barb). These data are used to calculate average heterozygosity (h), Nei's standard genetic distance (DN) and probability of exclusion (PE). Variability expressed as the average heterozygosity was lower in the Arabian (0.330 ± 0.066), while it was higher and almost the same in the Arab‐Barb (0.413 ± 0.071) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The genetic proximity of both autochthonous breeds BA and AB was also demonstrated using the FCA and the Bayesian clustering approach, which gives more precise information on breed relationships. However, our estimates for the native breeds (BA and AB) are similar to this reported by Ouragh et al (1994), pointed out using biochemical polymorphisms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The genetic proximity of both autochthonous breeds BA and AB was also demonstrated using the FCA and the Bayesian clustering approach, which gives more precise information on breed relationships. However, our estimates for the native breeds (BA and AB) are similar to this reported by Ouragh et al (1994), pointed out using biochemical polymorphisms.…”
Section: Discussionsupporting
confidence: 90%
“…However, our estimates for the native breeds (BA and AB) are similar to this reported by Ouragh et al . (), pointed out using biochemical polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Berber et al (2014) reported genetic proximity of both Barb and Arab-Barb breeds. These results corroborate those advanced by Ouragh et al (1994). The neighbor-joining clustering approach and the factorial correspondence analysis were used as efficient tools that give precise information on breed relationships (Figs.…”
Section: Factorial Correspondence Analysis For Analyzed Horse Breedssupporting
confidence: 77%
“…Investigation of blood group markers, protein, and DNA polymorphisms in North African subpopulations showed a pronounced genetic variation within the Barbs and the Arab-Barbs. Private alleles and high levels of heterozygosity were noted, however, no significant genetic differentiation was observed between Barb and Arab-Barb populations [ 26 , 27 , 28 , 29 ]. Likewise, apparent phenotypic differences distinguish the purebred Barb horse from the Arabian horse [ 1 , 23 , 25 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%